Education in Thailand and the challenging issues - Cleesuntorn, Athipat (Life Sciences and Environment Journal, 2014)
Abstract Education in Thailand is aimed to provide individuals with learning skills, selfmanagementability,problem-solvingskills,ICTliteracy,languageproficiencyandthe abilitytoworkwithothers.Intermsofinvestmentineducation,Thailandhasinvestedmore ineducationandtrainingthananyinotherareasofdevelopmentinthelast twentyyearsbut the outcomes of such investment haven’t reached the country’s educational goals yet.Despite of a long and a hard push in many crucial areas, education still remains achallenging. The challenging issues can be identified as, equal opportunity in education,quality of education, ethical education, science and technology, vocational education, andinternational schools. That is why during the past decade, the nation’s attention has againriveted on education.